Differentiation of aromatic, bittering and dual-purpose commercial hops from their terpenic profiles: An approach involving batch extraction, GC–MS and multivariate analysis. (December 2020) - Duarte, Lucas Mattos; Amorim, Tatiane Lima; Grazul, Richard Michael; de Oliveira, Marcone Augusto Leal
Graphical abstract: Highlights: The terpenic fraction of 25 different hop varieties was investigated by GC–MS. An ultrasound-assisted extraction method employing hexane as solvent was used. PCA was used to recognize patterns among the different hop varieties. Aromatic, bittering and dual-purpose hops were distinguished among samples. Abstract: Terpenes are one of the main classes of compounds in hops ( Humulus lupulus, L). They play an important role in brewing due to their central function, which is related to beer aroma. A screening of terpenes in several commercial hop varieties was carried out by gas chromatography coupled to mass spectrometry after employing a simple, straightforward and high throughput extraction method. A single batch extraction, using hexane as solvent, was employed to obtain the terpenic fraction of the hop samples. Nineteen terpenes were identified in analyzed samples with β-myrcene (2.22–45.30%), α-humulene (20.20–67.64%), and β-caryophyllene (9.97–24.62%) being the major terpenes in all samples. The studied system was multivariate modeled by principal component analysis. Based on the proposed approach, it was possible to correlate the terpenic hop profiles to their specific purpose in the brewing industry and to distinguish aromatic hops (high α-humulene content), bittering hops (high β-myrcene content), and dual-purpose hops (more complex and intermediate terpenic profile) among the samples.